It's complicated: A case report on a COVID-19-positive HIV patient presenting with rhabdomyolysis and acute kidney injury. (October 2020) - Foster, Allison; Khan, Zohaib; Siddiqui, Aisha; Singh, Sukhdev; Atere, Muhammed; Nfonoyim, Jay M
The SARS-Cov-2/COVID-19 pandemic in early 2020 has had a devastating impact on health systems around the world. While viral pneumonia remains the most common complication, reports are surfacing of cases with neurological, cardiac, and renal involvement. Even less is known about the implications in special high-risk populations. In this report, we discuss a unique case of an HIV-positive patient in New York City who presented with a 2-week history of worsening fatigue, cough, dyspnea, and myalgias and was found to have COVID-19 pneumonia and acute kidney injury. He was managed for severe uremic metabolic acidosis and electrolyte abnormalities with emergent hemodialysis and supportive therapy with subsequent improvement. Direct involvement of SARS-CoV-2 and pneumonia-induced rhabdomyolysis were identified as the precipitating factors of his acute kidney injury. The pathophysiologic mechanisms of acute kidney injury, SARS-CoV-2 renal tropism, and the impact of highly active antiretroviral therapy on COVID-19 pneumonia are discussed. We highlight the importance of clinician awareness of this potentially fatal complication of COVID-19 pneumonia, particularly in the HIV-positive population as early recognition and management can have favorable outcomes.